Hedonic Test on Pempek with Beta Carotene Fortification from Different Concentrations of Carrot Puree - Badrul, Ahlam Inayatullah; Aldilla Sari Utami; Nia Boru Ritonga; Ira Gusti Riani; Munir, Muhammad Abdurrahman (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Pempek is a traditional food from South Sumatra that is highly regarded and very popular among the people of Indonesia. This food is usually made with tapioca, minced fish, water, salt and MSG. This study aims to create an innovation, namely beta carotene fortification in pempek dough. Hedonic tests were conducted to determine the level of respondent preference for the addition of carrot concentration in terms of color, aroma, flavor and texture. This study employed a Completely Randomised Design (CRD) with four treatments and three replications, namely: P0 (0% carrot puree), P1 (5% carrot puree), P2 (10% carrot puree), and P3 (18% carrot puree). Hedonic test data were analysed statistically using analysis of variance, and further DMRT tests were conducted. The results of this study indicate that the addition of 10% carrots to making snakehead fish pempek has a very significant effect (P < 0.01) on improving the hedonic colour, taste, aroma, and texture. It can be concluded that the addition of carrot, up to 10% as a source of beta-carotene, in making pempek can increase the level of panellists' preference for colour, taste, aroma, and texture. The best treatment is the addition of 10% carrots to the formulation of snakehead fish pempek, in terms of its colour, taste, aroma, and texture. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and Production